Sosialisasi Kreasi Pembuatan Minuman Buko Pandan Untuk Meningkatkan Perekonomian Masyarakat Di Desa Aceh Perupuk Kecamatan Bandar Pusaka Kab. Aceh Tamiang - Siska Ramadhani; Aura Fitri Ismayanti; Mutia Febrianti; Yunita Wati; Wahyuni (Fusion: Jurnal Pengabdian kepada Masyarakat, 2024)
The creation of the pandan book drink is one of the efforts to improve the community's economy in the village of Aceh Kerupuk Koma, Bandar Pusaka District, Aceh Tamiang Regency, the aim of this activity is to introduce the drink, which is currently being widely traded and discussed both on social media and manually, point by introducing This modern drink, Koma, of course, the author hopes that the community can be helped to get innovations in trading in order to improve the economy of the community in the village. The method used in this activity is carried out by socializing Koma, giving Koma material and practicing directly. How is the process of making Pandan Book Drink to the village community? This activity point was carried out using qualitative descriptive methods and direct observation as a technique for obtaining point data. The results of the discussion showed that the village community was very enthusiastic and curious because of the village community's lack of knowledge about modern things. In the implementation of making this drink, ingredients are used that are easily available in the village, so it is not difficult for people who want to start making and selling this drink. In this activity, the community was guided directly by KKN students from the Jam'iyyah Mahmudiyah Islamic College of Tanjung Pura Langkat as the organizers of the activity and presenters. The public was given an explanation about the ingredients used in making buko pandan drinks, the manufacturing steps, packaging methods and sales techniques. With this activity, the author hopes that the public will gain insight and experience in making modern drinks and how to trade. Thus, the people in Perupuk Village, Kec. Bandar Pusaka Kab. Aceh Tamiang can feel the benefits of this activity and can help improve the economy not only by farming but also by trading.